2022
DOI: 10.1186/s12903-022-02076-7
|View full text |Cite
|
Sign up to set email alerts
|

Virtual consultations for oral surgery patients

Abstract: Background Following Covid-19, many departments have incorporated teledentistry into practice. As new consultation methods are introduced, it’s imperative that patients have as similar an experience with virtual consultations to ensure informed decision-making. This project evaluated patients' perceptions of video consultations and determined if patients seen virtually received the same standard of information by auditing compliance with sending patient information leaflets (PILs) following vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The main barriers to change within a healthcare setting include increased workload, inadequate staff commitment and their attitude towards the intervention, and lack of support and training [32]. A great help to overcoming these barriers may consist in a user friendly, time-efficient, and uncomplicated clinical mailbox: the use of email templates containing the hyperlinks to each digital information leaflet allows clinicians to "personalize" each patient's email in an efficient manner by deleting the notpertinent information [33]. Many software applications have been suggested, some of them requiring the use of complex devices for communication and others requiring the use of only a smartphone, and yet others combining a smartphone plus a tool able to correctly capture the images sent to the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…The main barriers to change within a healthcare setting include increased workload, inadequate staff commitment and their attitude towards the intervention, and lack of support and training [32]. A great help to overcoming these barriers may consist in a user friendly, time-efficient, and uncomplicated clinical mailbox: the use of email templates containing the hyperlinks to each digital information leaflet allows clinicians to "personalize" each patient's email in an efficient manner by deleting the notpertinent information [33]. Many software applications have been suggested, some of them requiring the use of complex devices for communication and others requiring the use of only a smartphone, and yet others combining a smartphone plus a tool able to correctly capture the images sent to the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…It can also promote oral health in patients of all age groups. 15 , 25 , 28 , 38 44 Telemedicine, including teledentistry, is an ever-expanding practice worldwide. It is projected to grow 20% additionally over the next five years and revenue growth from 38B dollars in 2018 to 130B dollars by 2025 in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the utilization and efficacy of teledentistry in different fields, reporting that this tool could enhance oral healthcare delivery. 5 9 For instance, a recent study indicated that using teledentistry for orthodontic treatment follow-up reduced the number of appointments and shortened the treatment time by improving appliance tracking. 10 Another study compared the diagnostic accuracy of teledentistry and clinical dental examination in pediatric dentistry, finding no significant difference between the two assessment methods.…”
Section: Introductionmentioning
confidence: 99%